2013
DOI: 10.1038/nbt.2713
|View full text |Cite
|
Sign up to set email alerts
|

Spatially isotropic four-dimensional imaging with dual-view plane illumination microscopy

Abstract: Optimal four-dimensional imaging requires high spatial resolution in all dimensions, high speed and minimal photobleaching and damage. We developed a dual-view, plane illumination microscope with improved spatiotemporal resolution by switching illumination and detection between two perpendicular objectives in an alternating duty cycle. Computationally fusing the resulting volumetric views provides an isotropic resolution of 330 nm. As the sample is stationary and only two views are required, we achieve an imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
322
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(322 citation statements)
references
References 45 publications
0
322
0
Order By: Relevance
“…+TIPs and their minus-end-associated counterparts (−TIPs) (Akhmanova and Hoogenraad, 2015), provides opportunities to test microtubule functions in 3D cell migration in a more specific way. Finally, the development of light-sheet microscopy and its recent application to microtubule plus-end dynamics in 3D (Chen et al, 2014;Wu et al, 2013;Yamashita et al, 2015) combined with the development of more sophisticated 3D tissue models, such as organoids (Shamir and Ewald, 2014), or with microfabricated and microfluidic devices (Paul et al, 2016), has initiated a new era of cytoskeletal studies in live cells that migrate in 3D environments. Important questions for future research include how microtubule-actin interactions, microtubule-related signaling, adhesion regulation and trafficking, and mechanical properties within soft 3D matrices compare to what is known from decades of 2D biology.…”
Section: Resultsmentioning
confidence: 99%
“…+TIPs and their minus-end-associated counterparts (−TIPs) (Akhmanova and Hoogenraad, 2015), provides opportunities to test microtubule functions in 3D cell migration in a more specific way. Finally, the development of light-sheet microscopy and its recent application to microtubule plus-end dynamics in 3D (Chen et al, 2014;Wu et al, 2013;Yamashita et al, 2015) combined with the development of more sophisticated 3D tissue models, such as organoids (Shamir and Ewald, 2014), or with microfabricated and microfluidic devices (Paul et al, 2016), has initiated a new era of cytoskeletal studies in live cells that migrate in 3D environments. Important questions for future research include how microtubule-actin interactions, microtubule-related signaling, adhesion regulation and trafficking, and mechanical properties within soft 3D matrices compare to what is known from decades of 2D biology.…”
Section: Resultsmentioning
confidence: 99%
“…A 450 nm wavelength blue laser diode module with 80 mW power was used in our experiment for the excitation of GFP samples. A tunable diaphragm with a 0.7 mm to 2 mm diameter clean aperture was used to control the vertical extent of the incident laser beam to further determine the axial confinement of the laser sheet as well as its confocal region, wherein the Gaussian laser sheet could be treated as uniform [13,19,20]. A 10mm x 20mm cylindrical lens with 30 mm focal-length lens was mounted at the end of the illumination path to generate a line-focused laser sheet on the horizontal plane.…”
Section: Design Of Horizontal Plane Illuminationmentioning
confidence: 99%
“…The former has been addressed by combining several views in multiview SPIM (mSPIM) [52,53], MuVi-SPIM [54], or dual-inverted SPIM (diSPIM) [55]. By contrast, low optical sectioning resolution has been recently addressed by altering the shape of the beam, noting that when using traditional Gaussian beams this focused light sheets imply smaller fields of view.…”
Section: Light Sheet Microscopymentioning
confidence: 99%
“…By contrast, low optical sectioning resolution has been recently addressed by altering the shape of the beam, noting that when using traditional Gaussian beams this focused light sheets imply smaller fields of view. To overcome this fact other beams have been explored, in particular Bessel beams [55] owing to their longer depth of focus and their 'self-reconstructing' capabilities which suffer less from the effect of scattering [49,50]. Recently, Vettenburg et al [56] have shown that the use of Airy beams may extend the field of view in scanned beam light sheet microscopes up to distances $40-fold greater than the field of view offered by a Gaussian beam and $fourfold that of a Bessel beam.…”
Section: Light Sheet Microscopymentioning
confidence: 99%